Balloon Dilation of the Eustachian Tube in Chronic Eustachian Tube Dysfunction: A Retrospective Study of 107 Patients - Oehlandt Heidi; Pulkkinen Jaakko; Haavisto Lotta (Mediterranean Society of Otology and Neuro-Otology, 2025)
BACKGROUND
Eustachian tube dysfunction affects from 1% to 5% of adults. This study evaluates the effectiveness of balloon dilation of eustachian tube for treating nonselected patients with eustachian tube dysfunction in a long term.
METHODS
We evaluated all balloon dilation of eustachian tube operations at Turku University Hospital from 2013 to 2016. The data from 107 patients and 167 ears were collected retrospectively and a questionnaire was sent to these patients regarding their symptoms.
RESULTS
An evident reduction of the symptoms was noticed. Aural fullness, otalgia, recurrent acute otitis media, or otitis media with effusion as well as symptoms from changes to ambient pressure and the ability to do the Valsalva maneuver were significantly improved. The mean followup time with the questionnaire was 33 months. Of patients, 80% (36/45) reported long-term reduction of symptoms.
CONCLUSIONS
In our study, balloon dilation of eustachian tube seems to have reduced symptoms of eustachian tube dysfunction and the results appear to be long lasting.